Seasonal changes in leaf conductance of three deciduous trees in response to drought - Tripathi, S; Shrestha, Bharat B; Jha, PK (Botanica Orientalis: Journal of Plant Science, 2007)
Botanica Orientalis Vol.4(1) 2004. p.55-58